PEDAGOGICAL OBSERVATION AND ANALYSIS (Multidisciplinary Journal of Science and Technology, 2025)
This article theoretically illuminates one of the main methods used in the process of pedagogical research - observation and its analysis methods. The purpose, types, stages and advantages of pedagogical observation are analyzed, and the necessary conditions for its effective implementation are indicated. Also, the scientific research, method, result, reflection, observer, diagnostics of observation methods in the study of the educational process are presented.